Radio Frequency Modulation Made Easy - Faruque, Saleh (SpringerBriefs in Electrical and Computer Engineering, 2017)
This book introduces Radio Frequency Modulation to a broad audience. The author blends theory and practice to bring readers up-to-date in key concepts, underlying principles and practical applications of wireless communications. The presentation is designed to be easily accessible, minimizing mathematics and maximizing visuals.